A Darwinian Study of Ammu’s Violent Behaviour in the ‘The God of Small Things’ - Nawaz, Muhammad (International Journal of English Literature and Social Sciences (IJELS), 2019)
This research intends to study the acts of violence in Arundhati Roy's debut novel The God of Small Things with special reference to the female characters. As a social and political activist, Roy has her own perception of violence that is reflected through her female characters especially through her chief protagonist Ammu, a divorced woman, who violates the social norms by having a secret love affair with an untouchable laborer. Thus all the four women in the novel, in one way or the other, evolve, adapt, resist and challenge the hegemonic powers and simultaneously modify the stereotypes about gender and violence. And by doing so, they confirm to the Darwinian approach that violence is innate in human nature, constrained by biology and concurrently embedded in culture.